Integrating wide-swath altimetry data into Level-4 multi-mission maps - M. Ballarotta; C. Ubelmann; V. Bellemin-Laponnaz; F. Le Guillou; G. Meda; C. Anadon; A. Laloue; A. Delepoulle; Y. Faugère; M.-I. Pujol; R. Fablet; G. Dibarboure (Ocean Science)
Real-time observation of ocean surface topography is essential for various oceanographic applications. Historically, these observations have mainly relied on satellite nadir altimetry data, which were limited to observation scales greater than approximately 60 km. However, the recent launch of the wide-swath Surface Water Ocean Topography (SWOT) mission in December 2022 marks a significant advancement, enabling the two-dimensional global observation of finer-scale oceanic scales (∼ 15 km). While the direct analysis of the two-dimensional content of these swaths can provide valuable insights into ocean surface dynamics, integrating such data into mapping systems presents several challenges. This study focuses on integrating the SWOT mission into multi-mission mapping systems. Specifically, it examines the contribution of the SWOT mission to both the current nadir altimetry constellation (six/seven nadirs) and a reduced nadir altimetry constellation (three nadirs). Our study indicates that within the current nadir altimetry constellation, SWOT's impact is moderate, as existing nadir altimeters effectively constrain surface dynamics. However, in a hypothetical scenario where a reduced nadir altimetry constellation is envisioned to be operational by 2030, the significance of wide-swath data in mapping becomes more pronounced. Alternatively, we found that data-driven and dynamical mapping systems can significantly participate in refining the resolution of the multi-mission gridded products. Consequently, integrating high-resolution ocean surface topography observations with advanced mapping techniques can enhance the resolution of satellite-derived products, providing promising solutions for studying and monitoring sea-level variability at finer scales. However, to fully exploit SWOT's capabilities, future research will need to focus on innovations in data gridding and assimilation to extend mapping beyond geostrophically balanced flows.